The Railway Corridor through Bolivia: A Lost Opportunity. - Guzman Ballivian, Luis Hugo Javier (Kaunas University of Technology, 2023)
The paper is focused on discussion of logistics and transport reality, comparing current conditions with what they could have been if the Central Bi-Oceanic Railway Corridor, also known as “The Panama Canal of the 21st Century” projected to join the Pacific and Atlantic Oceans in South America linking Brazil, Bolivia and Peru, had been built. The analysis will be carried out taking into consideration different aspects of paramount importance in the economic global context, focusing on operational costs, energy consumption, environment impact and a quantification of external costs.
Železniční koridor napříč Bolívií: promarněná příležitost
Keywords: bi-oceanic; railway corridor; South America; travel time; cost reduction; mezioceánský; železniční koridor; Jižní Amerika; cestovní čas; redukce nákladů